2019
DOI: 10.1108/ecam-07-2018-0277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organizational commitment on work–life balance and organizational performance of female construction professionals

Abstract: Purpose The purpose of this paper is to evaluate the mediating role of organisational commitment in the relationship between work‒life balance (WLB) and organisational performance of female construction professionals in the Nigerian construction industry. Design/methodology/approach The study empirically examined WLB of female professionals in medium- and large-sized Nigerian construction organisations. The data collected were analysed using partial least square structural equation modelling (PLS-SEM). Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 72 publications
4
48
2
9
Order By: Relevance
“…W the relationship between work-life balance and organizational commitment is examined, it is seen that work-life balance positively affects organizational commitment. These results are consistent with the literature (Vatansever, 2008;Sakthivel and Jayakrishnan, 2012;Gupta and Gupta, 2013;Azeem and Akhtar, 2014;Korkmaz and Erdoğan, 2014;Nayak and Sahoo, 2015;Dhammika, 2016;Wijaya ve Dewi, 2017;Oyewobi et al, 2019;Hutagalunga, Soeltonb and Octavianic, 2020;Kesumayani et al, 2020;Wardana et al, 2020). Again, according to the findings of the study, it is seen that work-life balance is sufficient on emotional, normative and continuation commitment.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…W the relationship between work-life balance and organizational commitment is examined, it is seen that work-life balance positively affects organizational commitment. These results are consistent with the literature (Vatansever, 2008;Sakthivel and Jayakrishnan, 2012;Gupta and Gupta, 2013;Azeem and Akhtar, 2014;Korkmaz and Erdoğan, 2014;Nayak and Sahoo, 2015;Dhammika, 2016;Wijaya ve Dewi, 2017;Oyewobi et al, 2019;Hutagalunga, Soeltonb and Octavianic, 2020;Kesumayani et al, 2020;Wardana et al, 2020). Again, according to the findings of the study, it is seen that work-life balance is sufficient on emotional, normative and continuation commitment.…”
Section: Findings and Discussionsupporting
confidence: 91%
“…The results indicate that Integrated motivation had a positive significant direct effect on Physical, Emotional and Cognitive engagement. These findings are marginally consistent with those of (Saks, 2006;Oudeyer et al, 2008;Rich et al, 2010;Malinowska et al, 2018). Finally, the results of the direct effects indicated that Method and Scheduling Autonomy had a positive significant direct effect on Emotional engagement, but no significant effect on neither Physical nor Cognitive engagement, thereby supporting the results of (Andrew & Sofian, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…The Four types of regulatory processes that represent extrinsic motivation are integrated motivation, identified regulation, interjected regulation, and external regulation; all differ in the level of internalization of extrinsic motivation (Fernandes, 2020). It has been shown that in comparison to extrinsic motivation, intrinsic motivation is related to many positive aspects of well-being, such as higher work enjoyment and work engagement (Malinowska et al, 2018), lower level of fatigue and burnout (Rich et al, 2010), lower level of anxiety (Oudeyer et al, 2008), and physical symptoms (Saks, 2006). The function of intrinsic work motivation is emphasized by (Chung & Jeon, 2020), who indicate that it is fundamental for the development of work engagement.…”
Section: Job Autonomy Autonomous Motivation and Employee Engagementmentioning
confidence: 99%
“…The effect of organizational commitment on performance is explained by the research of Oyewobi et al (2019), Chiu et al (2019), and Imamoglu et al (2019) who use structural equation modeling (PLS-SEM) as an analytical tool. Franco and Franco (2017) found that in family SMEs, affective commitment has a positive influence on contextual performance.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Research on organizational culture on commitment is explained by Al-Sada (2017), Raharjo et al (2018), Shim (2015) and Jain (2015) which explain that organizational culture has a positive influence on employee organizational commitment. An empirical study of the relationship between organizational commitment and performance is shown by research by Oyewobi et al (2019), Chiu et al (2019), Franco and Franco (2017).…”
mentioning
confidence: 99%